THE DETERMINANT OF DIVIDEND PAYOUT RATIO: LONG-TERM ANALYSIS IN BUKU EMPAT'S BANKS DURING PERIODS 2008 - 2017 - Aulia Rahma, Ayu; Dewi Syarif , Andam (Dinasti Publisher, 2020)
This research purposed to explored and analyzed those influence from capital adequacy ratios, net interest margins, loan to deposit ratios and non-performing loans towards dividend payout ratios on banks that registered as Buku Empat 2008-2017. Sampling gathered in this research by quantitative approach. Samples which obtained and used were Mandiri Bank, BRI, BNI, and BCA with observation period for 10 years. Data research was secondary data by panel data analysis method. The results shows that capital adequacy ratio had positive and significant influence towards dividend payout ratio, Net interest margin had negative and significant influence towards dividend payout ratio, Loan to deposit ratio had negative and significant impact on dividend payout ratio, non-performing loans had positive and significant impact towards dividends payout ratio.